On a theorem of Schur - Peter Hilton (International Journal of Mathematics and Mathematical Sciences)
We study the ramifications of Schur's theorem that, if G is a group such that G/ZG is finite, then G′ is finite, if we restrict attention to nilpotent group. Here ZG is the center of G, and G′ is the commutator subgroup. We use localization methods and obtain relativized versions of the main theorems.